Topological essentiality and nonlinear boundary value control problems^* - Górniewicz, Lech; Nistri, Paolo (Topological Methods in Nonlinear Analysis, 1999)
A concept of topological essentiality is used to prove several existence results for nonlinear boundary value control problems. Some examples to illustrate the obtained results are presented.